Acute myelogenous leukemia revealed by acute appendicitis - Sanae El Marzguioui; Sanae Benameur; Abdeladim Babakhouya; Maria Rkain; Noufissa Benajiba (Apollo Medicine)
Acute myelogenous leukemia can rarely involve the digestive tract. We report a case of a girl of 9 years old, admitted for surgical abdomen and operated for acute appendicitis. Complete blood count showed pancytopenia. The pathology study showed appendicular localization of acute myelogenous leukemia.